Assessment of Notch1 ligands production - key protein targets in breast cancer - Silva, Maria Margarida dos Santos (2014)
Cell-to-cell communication is required for many biological processes in development and adult life. One of the most common systems utilized by a wide range of eukaryotes is the Notch signalling pathway. Four Notch receptors and five ligands have been identified in mammals that interact via their extracellular domains leading to transcription activation. Studies have shown that the Notch ligands expression is undetectable in normal breast tissues, but moderate to high expression has been detected in breast cancer. Thus, any of the Notch1 ligands can be studied as possible therapeutic targets for breast cancer. To study Notch pathway proteins there is the need to obtain stable protein solutions. E. coli is the host of excellence for recombinant proteins for the ease of use, fast growth and high cell densities. However, the expression of mammalian proteins in such systems may overwhelm the bacterial cellular machinery, which does not possess the ability for post-translational modifications, or dedicated compartments for protein synthesis. Mammalian cells are therefore preferred, despite their technical and financial increased demands. We aim to determine the best expression and purification conditions for the different ligand protein constructs, to develop specific function-blocking antibodies using the Phage Display technology. Moreover, we propose to crystallize the Notch1 ligands alone and in complex with the phage display selected antibodies, unveiling molecular details. hJag2DE3 and hDll1DE6 proteins were purified from refolded inclusion bodies or mammalian cell culture supernatants, respectively, and purity was confirmed by SDS-PAGE (>95%). Protein produced in mammalian cells showed to be more stable, apparently with the physiological disulfide pattern, contrary to what was observed in the refolded protein. Several nano-scale crystallization experiments were set up in 96-well plates, but no positive result was obtained. We will continue to pursue for the best expression for the Notch ligand constructs in both expression systems.